2016
DOI: 10.1111/joor.12414
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral sensory deprivation of trigeminal afferent fibres on corticomotor control of human tongue musculature: a preliminary study

Abstract: Transcranial magnetic stimulation (TMS) has demonstrated changes in motor evoked potentials (MEPs) in human limb muscles following modulation of sensory afferent inputs. The aim of this study was to determine whether bilateral local anaesthesia (LA) of the lingual nerve affects the excitability of the tongue motor cortex (MI) as measured by TMS. The effect on MEPs after bilateral LA of the lingual nerve was studied, while the first dorsal interosseous (FDI) muscle served as a control in ten healthy participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The slope of the curve is interpreted as the measure of cortical excitability. Figure shows a schematic representation of the protocol implemented in these studies which demonstrate an increased performance with facilitation of MEPs and MI map areas after oral motor training paradigm . However, one may note that the relationship between excitability and the activity of the region is quite complex and the factors determining MI plasticity are not yet clear .…”
Section: Oral Motor Skill Acquisition and Training‐induced Neuroplastmentioning
confidence: 96%
See 3 more Smart Citations
“…The slope of the curve is interpreted as the measure of cortical excitability. Figure shows a schematic representation of the protocol implemented in these studies which demonstrate an increased performance with facilitation of MEPs and MI map areas after oral motor training paradigm . However, one may note that the relationship between excitability and the activity of the region is quite complex and the factors determining MI plasticity are not yet clear .…”
Section: Oral Motor Skill Acquisition and Training‐induced Neuroplastmentioning
confidence: 96%
“…Previous studies in rodents have suggested that the reorganisation of the MI may occur after peripheral nerve injuries . Further, experimental studies in humans have shown that manipulation of peripheral sensory inputs from oro‐facial structures alters the cortical excitability of the oro‐facial muscles …”
Section: Oral Motor Skill Acquisition and Training‐induced Neuroplastmentioning
confidence: 99%
See 2 more Smart Citations
“…The face sensorimotor cortex plays an important role in adaptive and learning processes in animals and humans . Previous studies have shown a reorganisation of the jaw and tongue motor representations or changes in motor cortex excitability following intra‐oral alterations or learning of novel oral motor tasks . More recent animal studies in rats have shown significant neuroplastic changes within the face motor cortex following modification of the dental occlusion .…”
Section: Introductionmentioning
confidence: 99%